2016
DOI: 10.1007/s12035-016-9717-5
|View full text |Cite
|
Sign up to set email alerts
|

Pramipexole, a Dopamine D2/D3 Receptor-Preferring Agonist, Prevents Experimental Autoimmune Encephalomyelitis Development in Mice

Abstract: Experimental autoimmune encephalomyelitis (EAE) is the most used animal model of multiple sclerosis (MS) for the development of new therapies. Dopamine receptors can modulate EAE and MS development, thus highlighting the potential use of dopaminergic agonists in the treatment of MS, which has been poorly explored. Herein, we hypothesized that pramipexole (PPX), a dopamine D2/D3 receptor-preferring agonist commonly used to treat Parkinson's disease (PD), would be a suitable therapeutic drug for EAE. Thus, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 67 publications
3
30
0
2
Order By: Relevance
“…Drd2 agonist was first reported to suppress nitric oxide and tumor necrosis factor-α in peripheral neutrophils two decades ago [32]. Since then, more studies have showed that Drd2 is a potential candidate for amelioration of inflammatory diseases [33][34][35][36] and NDDs [22,[37][38][39]. Nevertheless, to date there are no reports on whether Drd2 participates in the suppression of inflammasome activation.…”
Section: Discussionmentioning
confidence: 99%
“…Drd2 agonist was first reported to suppress nitric oxide and tumor necrosis factor-α in peripheral neutrophils two decades ago [32]. Since then, more studies have showed that Drd2 is a potential candidate for amelioration of inflammatory diseases [33][34][35][36] and NDDs [22,[37][38][39]. Nevertheless, to date there are no reports on whether Drd2 participates in the suppression of inflammasome activation.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is also associated with changes in brain dopamine metabolism (Felger, 2016); dopamine in turn affects immune system, especially immune response mediated by interleukin 17 producing Th cells (labelled Th17) that are distinct from Th1 and Th2 cells (Lieberknecht et al, 2016; Melnikov et al, 2016). Bupropion, a non-serotonergic antidepressant, inhibits dopamine reuptake, increases brain extracellular dopamine concentration (Ascher et al, 1995; Cremers et al, 2016), and has been shown to reduce inflammation mediated by both Th1 (by reducing IL-1 beta, IFNγ, and TNFα) and Th17 cells (Brustolim et al, 2006; Ebbinghaus et al, 2012; Warner-Schmidt et al, 2011).…”
Section: 0 Introductionmentioning
confidence: 99%
“…Dopamine D2 receptor (Drd2) has been regarded as a potential anti-inflammatory target in the therapy of NDDs [ 19 21 ]. Drd2 expresses both in neurons and astrocytes [ 22 ].…”
Section: Introductionmentioning
confidence: 99%